2016
DOI: 10.3389/fimmu.2016.00484
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Discriminate between Lipopolysaccharides of Different Bacterial Sources and Selectively Release Neutrophil Extracellular Traps

Abstract: The release of neutrophil extracellular traps (NETs), either during “suicidal” or “vital” NETosis, represents an important strategy of neutrophils to combat Gram-negative bacteria. Lipopolysaccharide (LPS), a major component of the outer membrane of Gram-negative bacteria, is a reported stimulus for NET formation. Although it is widely acknowledged that the structural diversity in LPS structures can elicit heterogeneous immune responses, species- and serotype-specific differences in the capacity of LPS to trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(164 citation statements)
references
References 49 publications
(52 reference statements)
6
157
0
1
Order By: Relevance
“…We have previously shown that elastase has proteolytic activity in NOX-dependent NETs, but not in NOX-independent NETs 10. Why the proteolytic activity of elastase differs between NOX-dependent and NOX-independent NETs is not completely clear, but is likely explained by the differential requirement of NOX-derived ROS during both pathways of NET formation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously shown that elastase has proteolytic activity in NOX-dependent NETs, but not in NOX-independent NETs 10. Why the proteolytic activity of elastase differs between NOX-dependent and NOX-independent NETs is not completely clear, but is likely explained by the differential requirement of NOX-derived ROS during both pathways of NET formation.…”
Section: Discussionmentioning
confidence: 95%
“…NOX-independent NETs were generated as described previously 10. NETs were either directly visualised and characterised by immunofluorescence microscopy or isolated with 5 U/mL micrococcal nuclease for further characterisation with ELISAs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To introduce the S. enteritidis, S. typhimurium and B. fragilis to rats, we prepared suspensions in the concentration of 1.0 McF standards, which corresponds to the concentration of 3×10 8 CFU/ml. The evaluation of macroscopic manifestations of ileum deficiency was performed on a scale from 0 to 8 in accordance with the criteria of Morris et al in the modification of Jagtap [17]: (0) no visible changes, (1) there are areas of hyperemia, (2) there are lesions having a diameter of 1 mm or less, (3) lesions having a diameter of 2 mm or less (number <5), (4) there is a defect having a diameter of 2 mm or less (number 5-10), (5) a defect having a diameter of 2 mm or less (>10), (6) there is a lesion, having a diameter of more than 2 mm (number <5), (7) there are lesions having a diameter greater than 2 mm (number 5-10); (8) lesions having a diameter greater than 2 mm (>10).…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…A recent discovery related to the ability of neutrophils to distinguish lipopolysaccharides from different bacterial agents and selectively release extracellular traps (NETs) is of great interest in studying the mechanisms of interaction of pathogenic microorganisms with immune system cells and their ability to influence the formation of NETs the concentration of SCFA, as a factor affecting the inhibition of inflammatory reactions in the intestine [6,7].…”
Section: матеріали та методи здійснили дослідження за кількісним підmentioning
confidence: 99%